All in the Family: An Examination of the Predictors of Visitation Among Committed Juvenile Offenders. (January 2020) - Young, Brae Campion; Hay, Carter
Scholarship highlights the importance of visitation in improving the lives of prisoners across numerous domains including mental health, adjustment to confinement, and postrelease success. Although research on adult inmates has examined factors that predict visitation, no such study exists for juvenile offenders. Moreover, because this existing research has relied largely on administrative data, no study has examined how family and social contexts affect visitation. Using data collected on 2, 345 youth who completed residential placement in Florida, the current study examined how qualities and histories of offenders and their families affect the likelihood, consistency, and sequencing of visits for juvenile offenders. The results suggest that youth's demographics and offending histories, as well as their family backgrounds and relationships, affect visitation. Directions for future research and implications for policy and practice are discussed.